2012
DOI: 10.1111/j.1533-2500.2012.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Piriformis Syndrome in Chronic Low Back Pain Patients. A Clinical Diagnosis with Modified FAIR Test

Abstract: Piriformis syndrome is a painful condition that is often overlooked in the differential diagnosis of chronic buttock or low back pain. The modified FAIR test together with piriformis muscle injection is potentially a reliable method for the clinical diagnosis of piriformis syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
2
33
0
1
Order By: Relevance
“…This study found a high proportion of patients (278 of 828, 33.6%) with paraspinal pain in the past month. However, in a clinical setting patients frequently present with gluteal pain[63, 64]. Thus, the small proportions with point or 1-month period prevalence of gluteal pain were unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a high proportion of patients (278 of 828, 33.6%) with paraspinal pain in the past month. However, in a clinical setting patients frequently present with gluteal pain[63, 64]. Thus, the small proportions with point or 1-month period prevalence of gluteal pain were unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Previous studies have shown that female suffer more from piriformis syndrome than male, although with varying proportions, Danilo et al found a ratio of female compared to male 6: 1, Chen et al reported a ratio of 3:2. 3,6 Predisposing female in piriformis syndrome may be caused by anatomical angle of the quadriceps femoris muscle in the women pelvis is wider than men. 7 Other studies reported that hormonal changes in women especially during pregnancy can also affect the occurrence of piriformis syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Park et al examined the relationship between BMI and piriformis muscular abnormalities in inactive populations through Computed Tomography (CT) imaging and concluded that an increase in BMI resulted increase in the distance between the piriformis muscle and the surrounding subcutaneous tissue. 6,9 These abnormalities might trigger the occurrence of piriformis syndrome. However, the correlation between the incidence of piriformis syndrome and the increase in BMI still requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…FBSS is characterized by recurrent or residual back pain after spinal surgery, and it has a reported incidence of 20-40% [56], which increases the likelihood of the patient suffering from PMS as part of the constellation of the painful symptoms. PMS is prevalent in 13.7% of the general population, in 17% of low LBP patients [57], and reaching 40.4% of chronic LBP post discectomy patients [13].…”
Section: Prevalence Of Fbss and Pmsmentioning
confidence: 99%